Weather Radar Insights Into the Turbulent Dynamics of a Wildfire‐Triggered Supercell Thunderstorm. Issue 15 (2nd August 2019) - Terrasson, Alex; McCarthy, Nicholas; Dowdy, Andrew; Richter, Harald; McGowan, Hamish; Guyot, Adrien
Abstract: Understanding wildfire‐atmosphere interactions is key to improved accuracy of predictions of wildfire behavior. This is needed for improved preparedness to mitigate loss of life and property during wildfire events, particularly for situations with strong fire‐atmosphere coupling. Here we present observations from the passage of a cold front over the Sir Ivan Dougherty wildfire on February 2017 in eastern Australia. We demonstrate that an increase in near‐surface atmosphere moisture associated with the cold front, when combined with changes in fire behavior at that time, led to reduced thermodynamic stability that helped to trigger a thunderstorm. This fire‐trigged supercell thunderstorm produced lightning, while radar observations identified a mesocyclonic circulation within the pyrocumulonimbus, similar to a supercell thunderstorm. Results highlight the need to monitor the thermodynamic properties of air masses approaching wildfires and the rapid evolution of pyrocumulonimbus, which may develop mesocyclone characteristics. Weather radar offers the most effective capability to achieve such insights. Plain Language Summary: Here we present observations of the behavior of a wildfire and associated meteorology over a large wildfire in eastern Australia. By analyzing weather radar data and meteorological data from close proximity to the fire, we show that an increase in atmospheric moisture due to the passage of a cold front over the fire ground, combined with changes in fire behavior at that time, was sufficient to trigger development of a wildfire‐induced thunderstorm. This fire‐generated storm produced lightning and began to rotate similar to a supercell thunderstorm. We conclude by highlighting the capability of weather radar in combination with standard meteorological observations to provide valuable insight to fire‐atmosphere coupling. These observations are essential to build understanding of extreme wildfire events for enabling improved prediction of their behavior to reduce loss of life and property in firestorms. Key Points: Genesis, growth, and decay of a pyroconvective thunderstorm are studied combining ground weather radar, atmospheric profiling, and micrometeorological observations Observations of fire‐atmosphere interactions enable quantification of pyroconvective thunderstorm turbulence and kilometer‐scale vortices An "optimal" window of conditions is identified for a fire to trigger thunderstorm genesis and generate lightning that can ignite new fires